Síntese enantiosseletiva da sertralina: estudo e proposta de nova rota quimioenzimática - Mugnaini, Ingrid Christovam [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Sertraline is one of the most important drugs in the psychotropic industry, and its use has been approved in the treatment of various psychological conditions. It belongs to the class of Selective Serotonin Reuptake Inhibitors (SSRIs), which act in order to increase the levels of serotonin in the synaptic cleft and are called selective because they do not have significant activity in other neurotransmitters. Its three-dimensional structure has two stereogenic centers, therefore, there are four stereoisomers: cis- (1S, 4S)-, cis-(1R, 4R)-, trans-(1S, 4R)- and trans-(1R, 4S)-, being only the first one of industrial interest. Enantiomeric purity is known in the industry as an important factor in guaranteeing the safety of the drug and, thus, the search for synthetic routes that results in products with high yield value and enantiomeric excess is growing. In this context, the present work presents and evaluates in detail the industrial synthesis of Zoloft®️, from its first synthetic route to the one currently used, in addition to two other chemoenzymatic proposals existing in the literature and suitable for green chemistry. At the end, a new chemoenzymatic proposal is presented, which has as main stage the Dynamic Kinetic Resolution of a secondary alcohol through enzyme (Candida antarctica lipase B) combined with an inorganic salt (vanadyl sulfate). This step is based on the methodology developed by Milagre Research Group for the enantioselective synthesis of chiral secondary alcohols and offers as main advantages the lower monetary investment, less damage to the environment and ease of handling, in addition to the possibility of recycling and reusing the catalysts.

A sertralina (Zoloft®️) é um dos medicamentos mais importantes na indústria de psicofármacos, tendo seu uso aprovado no tratamento de diversas condições psicológicas. Pertence à classe dos Inibidores Seletivos de Recaptação de Serotonina (ISRS), que atuam de forma a aumentar os níveis de serotonina na fenda sináptica e são chamados seletivos por não possuírem atividade significativa em outros neurotransmissores. Sua estrutura tridimensional conta com dois centros estereogênicos, portanto, existem quatro estereoisômeros: cis-(1S, 4S)-, cis-(1R, 4R)- , trans-(1S, 4R)- e trans-(1R, 4S)-, sendo apenas o primeiro de interesse industrial. A pureza enantiomérica é conhecida na indústria como um importante fator para a garantia da segurança do fármaco e dessa forma, a busca por rotas sintéticas que tem como resultado produtos com alto valor de rendimento e excesso enantiomérico é crescente. Nesse contexto, o presente trabalho apresenta e avalia de forma detalhada a síntese industrial do Zoloft®️, desde sua primeira rota sintética até a utilizada atualmente, além de outras duas propostas quimioenzimáticas existentes na literatura e adequadas à química verde. Ao final, é apresentada uma nova proposta quimioenzimática, que tem como etapa principal a Resolução Cinética Dinâmica de um álcool secundário através de enzima (lipase B de Candida antarctica) combinada a um sal inorgânico (sulfato de vanadila). Essa etapa é baseada na metodologia desenvolvida pelo Milagre Research Group para a síntese enantiosseletiva de álcoois secundários quirais e oferece como principais vantagens o menor investimento monetário, menor dano ao meio ambiente e facilidade de manuseio, além da possibilidade de reciclagem e reutilização dos catalisadores.
Enantioselective synthesis of sertraline: study and proposal of a new chemoenzymatic route
Keywords: Biocatálise; Catálise; Química verde; Síntese orgânica